The Consumption of Energy Drinks Induces Blood-Brain Barrier Dysfunction in Wild-Type Mice - Graneri, Liam; Lam, Virginie; D'Alonzo, Zachary; Nesbit, Michael; Mamo, John C. L.; Takechi, Ryusuke (Frontiers in Nutrition, 2021)
Energy drinks containing significant quantities of caffeine and sugar are increasingly consumed, particularly by adolescents and young adults. Chronic ingestion of energy drinks may potentially regulate vascular risk factors. This study investigated the effects of chronic ingestion of energy drinks on blood-brain barrier (BBB) integrity and neuroinflammation. Male C57BL/6J mice were maintained on water (control), MotherTM (ED), sugar-free MotherTM (sfED), or Coca ColaTM soft drink (SD) for 13 weeks. The BBB integrity and neuroinflammation were analysed with semi-quantitative immunofluorescent microscopy. Blood pressure, plasma inflammatory cytokine levels and blood glucose were also considered. Following 13 weeks of intervention, mice treated with ED, sfED, and SD showed significant disruption of BBB. However, marked neuroinflammation was observed only in sfED group mice. The consumption of ED and sfED significantly altered the blood pressure and plasma concentrations of inflammatory cytokines, TNF-a, IL-4, IL-6 and IL-10 and both increased plasma glucose. Correlation analyses showed significant associations between BBB dysfunction and hypotension, hyperglycaemia and cytokine dyshomeostasis. The intake of energy drink, particularly the sugar free formulation, may compromise the integrity of BBB and induce neuroinflammation via hypotension, hyperglycaemia and inflammatory pathways.